Brand Image, Kualitas Produk dan Persepsi Harga terhadap Pembelian Ulang Produk pada KFC (Kentucky Fried Chicken) di Kabupaten Jember - Eka Atikhah Putri Badzillina; M. Naely Azhad; Jekti Rahayu (IPM2KPE, 2024)
This research aims to investigate the influence of Brand Image (X1), Product Quality (X2), and Product Repurchase (X3) on Repurchase. Descriptive and associative methods were used, with data collection through questionnaires and interviews. Data analysis involves descriptive statistical tests, data instruments, validity and reliability, as well as classic assumptions such as normality, multicollinearity and heteroscedasticity tests. Multiple linear regression, t test, and coefficient of determination were used to analyze the data. The results show that Brand Image (X1), Product Quality (X2), and Price Perception (X3) together influence repeat purchases (Y) by 47.5% (0.475), while 52.5% is influenced by these factors. others are outside the scope of the research. In conclusion, this research provides insight into the factors that influence repeat purchases and their relevance in the market context. Keywords: Brand Image, Product Quality, Price Perception, Repeat Purchase